Circular RNA CREBBP Suppresses Hepatic Fibrosis Via Targeting the hsa-miR-1291/LEFTY2 Axis - Yang, Ya-Ru; Hu, Shuang; Bu, Fang-Tian; Li, Hao; Huang, Cheng; Meng, Xiao-Ming; Zhang, Lei; Lv, Xiong-Wen; Li, Jun (Frontiers in Pharmacology, 2021)
CircRNAs (circRNAs) are commonly dysregulated in a variety of human diseases and are involved in the development and progression of cancer. However, the role of circRNAs in hepatic fibrosis (HF) is still unclear. Our previous high throughput screen revealed changes in many circRNAs in mice with carbon tetrachloride (CCl4)-induced HF. For example, circCREBBP was significantly down-regulated in primary hepatic stellate cells (HSCs) and liver tissue of HF mice induced by CCl4 compared to those in the vehicle group. Overexpression of circCREBBP with AAV8-circCREBBP in vivo prevented CCl4-induced HF worsening by reducing serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) contents, liver hydroxyproline levels, collagen deposition, and levels of pro-fibrosis genes and pro-inflammatory cytokines. Furthermore, in vitro function loss and function gain analysis showed that circCREBBP inhibited HSCs activation and proliferation. Mechanically, circCREBBP acts as a sponge for has-miR-1291 and subsequently promotes LEFTY2 expression. In conclusion, our current results reveal a novel mechanism by which circCREBBP alleviates liver fibrosis by targeting the has-miR-1291 /LEFTY2 axis, and also suggest that circCREBBP may be a potential biomarker for heart failure.